Determinants of Financial Literacy on Micro Waqf Banks in Aceh - Amrizal Hamsa; Arroyyan Ramly (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2022)
In comparison to the conventional financial literacy index, the Islamic financial literacy index in Aceh remains relatively low at 18.64%. The presence of micro Waqf banks in Aceh is intended to be beneficial to both urban and rural communities. This study investigates the factors that influence the public's preference for Micro-Wakaf Bank in Aceh. To collect data, a questionnaire was administered to 100 respondents throughout Aceh. This study utilizes the variables literacy index, preference, religiosity, and business motivation. To investigate these variables, a quantitative approach with multiple regression analysis techniques is employed. The results indicate that preference, religiosity, and business motivation have positive and statistically significant effects on Islamic financial literacy. Despite 52 percent Islamic financial literacy for micro waqf banks and the role of micro-waqf banks in expanding micro-scale businesses, the public preference for micro waqf banks remains low compared to Islamic banks. Because the practical implications of this research will have an impact on micro-waqf banks, as literacy numbers increased, the public will be more likely to choose micro-waqf banks for their business ventures.==================================================================================================== ABSTRAK – Determinan Literasi Keuangan terhadap Bank Wakaf Mikro di Aceh. Indeks literasi keuangan Syariah di aceh masih tergolong rendah sekitar 18,64% dibandingkan dengan indeks literasi keuangan konvensional. Hadirnya bank wakaf mikro di Aceh berupaya untuk meningkatkan kesejahteraan masyarakat urban dan pedesaan. Tujuan penelitian ini untuk menganalisis faktor-faktor yang mempengaruhi minat masyarakat Aceh dalam memanfaatkan bank wakaf mikro terhadap pemodalan usaha. Penelitian ini mengunakan metode kuantitatif dengan teknik analisis regresi berganda. Data penelitian dikumpulkan melalui kuesioner terhadap 100 responden yang tersebar di seluruh Aceh. Variabel yang digunakan dalam penelitian ini ialah indeks literasi, preferensi, religiusitas dan motivasi usaha. Metode analisis data menggunakan analisis regresi linear berganda. Hasil penelitian ini menunjukkan bahwa variabel preferensi berpegaruh positif dan signifikan terhadap indeks literasi keuangan syariah. Preferensi public terhadap bank wakaf mikro masih rendah dibandingkan dengan bank syariah, namun literasi keuangan syariah terhadap bank wakaf mikro sebesar 52% dan membantu peningkatan bisnis berskala mikro di dalam masyarakat. Oleh karenanya, hasil kajian ini berimplikasi bagi bank wakaf mikro dalam kepercayaan publik, dimana semakin tinggi tingkat literasi, semakin besar minat publik dalam memilih lembaga bank wakaf mikro dalam pemodalan usaha mereka.